Single Cell RNA Sequencing (scRNA-Seq) as an Emerging Technology in Cancer Research: Applications of scRNA-seq in cancer research - Rehman, Atta Ur; Rashid, Abdur; Anwar, Ijaz (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2021)
RNA sequencing (RNA-seq) has revolutionized basic biomedical research by studying the transcriptome at high resolution, and thus it has been proved to be very successful for understanding the molecular mechanisms of cancers. For example, RNA-seq has facilitated a comprehensive and multidimensional mapping of the key genomic changes that lead to various types of cancers. Nevertheless, the heterogeneous nature of cancer tissues has always been a problem. To overcome this challenge, single-cell RNA sequencing (scRNA-seq) has emerged as the most powerful tool to characterize cancer tissues by enhancing our knowledge of transcriptome at a single-cell resolution. In addition to disentangling the heterogeneity problem, scRNA-seq has other applications such as determining the molecular mechanisms of cellular differentiation, characterizing gene expression levels, and determining rare cell types found within cancer tissue. scRNA-Seq is used, as an emerging diagnostic tool, in tertiary healthcare settings with diverse clinical applications. Thus, the utility of scRNA-Seq in a healthcare system not only provides compelling evidence about understanding cancer biology but also points towards the development of therapeutic options in the future. The purpose of this review is to educate readers about the applications of scRNA-seq in cancer research in a wider context..